The Ambivalence of the Sacred: By R. Scott Appleby. (Boulder: Rowman & Littlefield Publishers, Inc., 1999. 429 pages.) (American Journal of Islam and Society, 2001)
The Ambivalence of the Sacred book attempts to articulate a framework forformulating specific answers, on a case-by-case basis, to three overarchingquestions pertaining to the seemingly ambivalent relationship betweenreligion and violence. First, it seeks to examine conditions under whichreligious actors become violent; secondly, the opposite circumstancesunder which religious actors reject the violence of religious extremistsaccording to the same principles of religious sanctity; and thirdly, thesettings in view of which non-violent religious actors can become agents ofpeacebuilding. The purported goal is to identify and develop means andmethods by which religion may become an instrument of conflict managementand/or resolution instead of being a source of deadly conflicts.Appleby argues that religion can be administered in such a prudent,selective, and deliberate fashion so as to allow it consistently to contributeto a peaceful resolution of conflicts. Additionally, that a new formof conflict transformation --"religious peacebuilding'- is actually takingshape among local communities plagued with violence. In this sense"ambivalence of the sacred projects an awareness that both possibilitiesof life and death reside within the holy.The book is divided into two parts. The first part (chs. 1-5) attempts toelaborate elements of a theory of religion's role in deadly conflict and toaddress the first two overarching questions above. Citing the cases of SouthAfrica and the transformations in Roman Catholic teachings, in response toboth state apartheid violence in the former, and to post-war era pressuresfor pluralism on the latter, chapter 1 examines the paradoxical and ambivalentlogic of the sacred. Chapters 2 and 3 explore the conditions underwhich religious actors legitimate violence as a sacred duty or privilege inlight of the violent forces of ethno-nationalism and religious extremism.Chapter 4 examines the phenomenon of nonviolent religious militancy bylooking at Buddhist peacemaking in Southeast Asia and by introducingtransnational NGO's that work with and among local religious actors. The ...